Her secret Rio baby - DaRosa, Luana (Harlequin medical romance, 2022)
An impulsive night of passion... A life-changing consequence! The night surgeon Eliana Oliveira met Diego Ferrari, he was just a handsome stranger in a bar in Rio de Janeiro. And acting on their instant attraction was the perfect escape from the shock of inheriting a whole hospital from her estranged late father. Now, on her first day at Santa Valeria General, she's in for two shocking discoveries: first, coming face-to-face with Diego in the operating room, and second, that she's expecting his baby!